Laser lithotripsy using dusting technique (low energy, high frequency) for symptomatic upper urinary tract stones - A. Ashmawy (SpringerOpen, 2021)
Abstract Background A prospective study to assess the feasibility of stone dusting technique (low energy and high frequency) during laser lithotripsy in symptomatic upper urinary tract |(UUT) stones. Methods Sixty patients with symptomatic single or multiple UUT stones less than 3 cm in diameter were included. Patients with coagulation disorders and active UTIs were excluded. All patients were clinically evaluated and underwent non-contrast spiral CT (NCSCT) to detect stone site, size, number, Hounsfield unit. A rigid or flexible ureteroscope was used with stone dusting using the Ho: YAG laser at low-energy and high-frequency (0.5 J & 20 Hz) set. Operative and fluoroscopy time, total energy delivered, type of stent, hospitalization time, complications and its grade, and stone-free rate using NCSCT after 4 weeks were recorded. Results The mean stone size ± SD (range) was 1.55 ± 0.55 (0.5–3) cm; out of sixty patients (50 with single stone and 10 with multiple stones), fifty-five patients were stone-free at 4 weeks. Complications had occurred in 11 patients (eight with grade I, one with grade II, and two with grade IIIa) according to Clavien–Dindo grading of surgical complications. Stone size was the only parameter which correlated significantly with stone-free rate. No significant correlation was found between incidence of complications and other parameters (stone size, site, BMI, age and operative time). Conclusions Stone dusting technique is feasible, safe and effective in management of UUT stones.